Giving and sorting among friends: evidence from a lab-in-the-field experiment - Binzel, Christine; Fehr, Dietmar (Economics letters, 2013)
We examine dictator giving in a lab-in-the-field experiment in Cairo. Giving to a stranger and to a friend is positively correlated, and more altruistic dictators increase their giving less under non-anonymity. However, friends’ altruistic preferences are not significantly correlated.
Gesehen am 26.06.2023